Emily Dickinson as a Lesbian Poet - An Analytical Study - Maragathavel, K. (International Journal of Psychosocial Rehabilitation, 2020)
This paper primarily focuses Emily Dickinson as a lesbian poet throwing the light on the male dominated society that curbed the women. It further aims to understand the inequality that exists in gender and focuses on power relation and sexuality. It is concerned with the ‘marginalization of women. It represents one of the most important social economic and aesthetic references at modern times. Further it examines women from all races, classes and culture. It is also manifesting how Emily Dickinson considers male as a sustained and she completely avoids. This paper will be an eye opener for the present women in the society. As the paper is in progress the reader may understand the hidden qualities, the power and the spirit of the women. It further showcases the self identified lesbian poets, especially Emily Dickinson.